HOW THE BILINGUAL BOOK DICTIONARY INFLUENCES THE VOCABULARY MASTERY FOR JUNIOR HIGH SCHOOL STUDENTS - admin admin; Yasmin Shofiyati (DIDAKTIKA, 2012)
Learning English as a foreign language (EFL) has a basic aspect which is vocabulary mastery. The writer considers that adolescent students have difficulties related to the process enriching their vocabulary. Bilingual dictionary could help the junior high students since it involves the first language. The first language will ease the students in figuring out the appropriate meaning proper with the context. Bilingual dictionary itself comes in various forms. There are computerized bilingual dictionary, electrical bilingual dictionary, and bilingual book dictionary. The writer consider bilingual dictionary as the aid for the junior high school students to gain their mastery in vocabulary. Bilingual dictionaries are popular among learners at all levels (Atkins & Varantola 1998; Baxter 1980). Learners of all proficiency levels can use bilingual dictionaries to learn vocabulary (Hulstijn, Hollander, & Grenadius 1996; Knight 1994). Bilingual book dictionary is applicable for the students in the school since bilingual book dictionary is affordable for the students. Bilingual dictionary is chosen by the writer because it involves the first language (L1) of the students. It eases them to find the appropriate meaning of the words. In bilingual book dictionary there are several meanings, part of speech, collocation, and the examples in the sentences. Those are the reason why the writer suggests the bilingual book dictionary as the best aid for the junior high school students in Indonesia to increase their vocabulary mastery.